ANALISIS EFEKTIVITAS PEMBELAJARAN AKTIF PAI BK TERHADAP PENGUASAAN MATERI ASMAUL HUSNA KELAS 2 SD - Ananda, Anisa; Al Raihan, Muhammad Alif; Putri Silma, Amelia; Syahbudi, Muhammad Reza; Abdul Fadhil (STAI Pelabuhan Ratu, 2024)
This study aims to analyze the effectiveness of active learning strategies in Islamic Education (PAI) textbooks on the mastery of Asmaul Husna among 2nd-grade elementary school students. A library research method was employed by collecting and analyzing relevant literature, such as journals, textbooks, and academic articles. The findings indicate that active learning methods, such as singing, group discussions, and visual media, significantly enhance students' understanding of the abstract concept of Asmaul Husna. These methods also boost students' engagement in learning, foster social skills, and facilitate the internalization of Asmaul Husna's values in daily life. Major challenges include limited teaching resources and teachers' competencies, which can be addressed through training and resource provision. The study concludes that active learning strategies are effective in improving students' comprehension of Asmaul Husna and are relevant for application in elementary Islamic education.